The Influence of Oceanic Stochastic Forcing on the Atmospheric Response to Midlatitude North Pacific SST Anomalies. Issue 17 (12th September 2018) - Sun, Xuguang; Tao, Lingfeng; Yang, Xiu‐Qun
Abstract: The stochastic sea surface temperature (SST) anomalies are always present because of the internal oceanic variability due to small‐scale SST variability and based on a set of ensemble experiments forced by Pacific Decadal Oscillation‐related midlatitude North Pacific SST anomalies with and without oceanic stochastic forcing, their influences on atmospheric variability in coarse‐resolution models are investigated in this study. Comparisons of experiment results show that oceanic stochastic forcing can improve the simulated atmospheric response by generating more organized atmospheric transient eddies through the increases of both thermal activity and atmospheric baroclinicity, similar to the high‐resolution observations and simulations. Dynamic diagnostics further reveal the dominant contributions of corresponding transient eddy vorticity forcing to the significantly enhanced westerly wind with equivalent barotropic structure. It suggests that the oceanic stochastic forcing is important and nonnegligible for the understanding and theory of oceanic feedback to the atmosphere in the midlatitudes. Plain Language Summary: The atmospheric response to the midlatitude North Pacific sea surface temperature (SST) anomalies are essential albeit weak for understanding the associated air‐sea interaction there, wherein storm track plays an important role. To adequately capture the storm tracks and large‐scale atmospheric structures as well, high‐resolution SST with detailed oceanic fronts and eddies are required in fine‐resolution atmospheric general circulation models. One of the important effects of high‐resolution SST is to enhance the atmospheric transient eddies by introducing more internal oceanic variabilities, which can be obtained by an alternative way in this study, that is, adding extra oceanic stochastic forcing in a coarse‐resolution atmospheric general circulation model. A set of ensemble experiments and dynamic diagnostics illustrate that oceanic stochastic forcing can generate many more atmospheric transient eddies through the increases of thermal activity and atmospheric baroclinicity, and further enhance large‐scale atmospheric response to the midlatitude North Pacific SST anomalies. Without increasing the amount of oceanic fronts and eddies and the capability of resolving the atmospheric transient eddies, this study illustrates that the oceanic stochastic forcing is important and nonnegligible for the understanding and theory of oceanic feedback to the atmosphere in the midlatitudes. Key Points: Oceanic stochastic forcing can produce organized large‐scale atmospheric structures as well as strengthened atmospheric transient eddies Storm tracks serve as the bridge between ocean stochastic forcing and the large‐scale atmospheric response Introducing oceanic stochastic forcing can advance the understanding and theory of oceanic feedback to the atmosphere in the midlatitudes